Resource mapping amid climate crisis for protection of hunter gatherer community livelihoods in Northern Tanzania - Bwagalilo, Fadhili (Frontiers in Climate, 2026)
This paper examines the urgent need for integrated resource mapping to protect the livelihoods of Hunter-Gatherer (H&G) communities in northern Tanzania amid the escalating impacts of climate change. Focusing on the Akie and Hadzabe peoples residing in Manyara Region, the study employs ethnographic observation, focus group discussions, and participatory geographical information systems to analyze land use patterns and climate dynamics. Findings reveal that climate change, coupled with increased agricultural expansion and population pressures, has significantly disrupted traditional H&G mobility, resource access, and cultural practices. Once mobile communities reliant on hunting, honey, fruits, and roots are now increasingly confined to smaller areas, with women and children especially burdened by the search for diminishing resources. The shift from bushland and grassland to agriculture has degraded wildlife habitats, reduced beehive trees, and fueled land use conflicts with neighbouring pastoral and farming groups. These changes threaten not only the food security and cultural identity of H&G communities but also their very survival. The paper argues that current village-based land use plans are insufficient and sometimes exacerbate conflicts. It recommends that integrated resource mapping, which considers traditional livelihood routes and resource zones beyond administrative boundaries, is essential for safeguarding the rights and livelihoods of H&G communities and ensuring sustainable co-existence with other land users in the region.